Social Policy Review 35 Analysis and Debate in Social Policy, 2023 - Cefalo, Ruggero; Rose, Marcia; Jolly, Andy (Policy Press, 2023)
EPDF and EPUB available Open Access under CC-BY-NC-ND licence. In the latest edition of Social Policy Review, experts review the leading social policy scholarship from the past year. The book addresses current issues and critical debates within the field, with a particular focus on intergenerational research. Published in association with the Social Policy Association, this comprehensive volume will be essential reading for students and academics in social policy, social welfare and related disciplines.